De Haas-van Alphen effect and superconductivity - Gor`kov, Lev P.; Landau, L. D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The problem of the robust de Haas-van Alphen oscillations seen experimentally in mixed superconducting state is discussed. The new threshold mechanism is suggested to explain persistence of the quantum oscillations deep in the superconducting state.